PERANCANGAN APLIKASI BERBASIS WEB UNTUK MEMETAKAN PENYAKIT PADA PUSAT KESEHATAN MASYARAKAT - Buntaran, Melvern (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The development of information technology can be used to assist the health sector. One of the organizers of the health services community health centers. To assist health centers in preparing a program of activities in the areas they then developed a web-based application for mapping disease. Method of application development using SDLC. Mapping results in the form of charts, tables, and maps that present data 10 major diseases. For mapping using Google Maps. Based on data from 2015 obtained from samples taken puskesmas Mandala 1000 data. After the classification of the disease was obtained information for most consecutive top 10 is influenza, dengue fever, accident injuries, diarrhea, typhoid fever, phlegm, cough, diabetes, and cholesterol. From the results of the classification of the information shown in the form of tables, graphs, and maps. It is hoped the information can help health centers to develop programs of health activities in their working area.